Automated Translation of Chinese-to-English Creative Literature - Hoover, Carl; Sommer, Heather (My University, 2010)
Preliminary research reveals that current work in the machine translation of Chinese-to-English focuses entirely on a statistical approach. This approach does not allow for a culturally-sensitive translation with regards to the source language, as meaning is often lost through metaphor or folklore references. This project explored the option of compiling a database to allow for the corpora analysis of creative works previously translated and employing an example-based approach to translation in conjunction with the currently popular statistical approach.
Color poster with text, diagrams, and map.
Keywords: Translating machines--Evaluation; Translating machines--Research; Chinese literature--Translations into English--Evaluation.; Translating and interpreting--Computer programs--Evaluation; Translating and interpreting--Computer programs--Research; Posters